Pain Modulation and Autonomic Function: The Effect of Clonidine. Issue 7 (17th February 2016) - Nahman-Averbuch, Hadas; Dayan, Lior; Sprecher, Elliot; Hochberg, Uri; Brill, Silviu; Yarnitsky, David; Jacob, Giris
Abstract: Objective . The α2 -agonist clonidine is an analgesic agent, whose yet uncertain action may involve either increase in pain modulation efficiency, change in autonomic function, and/or decrease in anxiety level. The present study aimed to examine the effect of oral clonidine on pain perception in healthy subjects in order to reveal its mode of action. Design . Randomized, double-blind, placebo-controlled study. Subjects . Forty healthy subjects. Methods . Subjects received either 0.15 mg oral clonidine or placebo. We measured pain parameters of heat pain thresholds, tonic heat stimulus, mechanical temporal summation, offset analgesia (OA) and conditioned pain modulation (CPM); autonomic parameters of deep breathing ratio and heart rate variability indices obtained before, during, and after tonic heat stimulus; and psychological parameters of anxiety and pain catastrophizing. Results . Clonidine decreased systolic blood pressure ( P = 0.022) and heart rate ( P = 0.004) and increased rMSSD ( P = 0.020), though no effect was observed on pain perception, pain modulation, and psychological parameters. Autonomic changes were correlated with pain modulation capacity; for OA, the separate slope model was significant ( P = 0.008); in the clonidine group, more efficient OA was associated with lower heart rate (r = 0.633, P = 0.005), unlike in the placebo group. Conclusions . The change in autonomic function that was related to the increase in pain modulation capacity, and the lack of change in anxiety, suggest a combined modulatory-autonomic mode of analgesic action for clonidine.